La adopción homoparental en el Ecuador y su relación con los principios de igualdad y no discriminación y del interés superior del niño (a). - Quezada Valdivieso, Robin Fernando (2023)
Since the emerging of children’s adoption, countless number of disputes have arisen on this issue, due to the fact that this process primary objective is to provide a dignified life for the adoptee and thus grant them a family. However, the concept of the family has not remained, and so with the passing of time, this figure was changing and most legislations prospered by regulating same-sex marriage, therefore highlighting the variety of families and giving a unique change to the conventional model of a family, that has historically been constituted by a man and a woman, to the diversity that meets human rights obligations. However, in Ecuador, the legislation expressly prohibits same-sex adoption, leading to discrimination against people who have a different sexual orientation or preference, which incurs in a violation of the right to equality and non-discrimination of couples established between same-sex people. In addition, this prohibition restricts the opportunity for children and adolescents to find a foster home and access to having a family and the implication of the joy and benefits they provide, such as the right to identity, inheritance and sustenance. Consequently, a non-experimental investigation was conducted using a descriptive level and cross-sectional method. The research was developed using a mixed approach, combining qualitative and quantitative methods. It should be noted that, from the qualitative aspect, a thorough review and critical study of the doctrine, jurisprudence and laws related to same-sex adoption in Ecuador was performed. On the other hand, in the quantitative aspect, a statistical analysis of the information collected was also carried out. It is worth mentioning that, in order to achieve the research objectives, a variety of methods were used, including inductive-deductive, analytical-synthetic, historical-logical, dogmatic and comparative. The findings of this research evidenced the current reality of same-sex adoption in Ecuador. Demonstrating that the prohibition of same-sex adoption is clearly contrary to the principles and the right to equality and non-discrimination, which is enshrined in national and 4 international law. Likewise, it was found that this prohibition is depriving children of the opportunity to integrate into a family and enjoy each and every one of the benefits that this entails. It is concluded that the prohibition of adoption by same-sex couples in Ecuador is discriminatory and contrary to the principles of equality and non-discrimination, as well as the best interests of the child. These results support the need to review and amend existing legislation to ensure equal rights and opportunities for all couples, regardless of their sexual orientation, and to ensure the well-being of children and the exercise of their right to a family and other related.